Surface Modification of Linen Fabric via UV Induced Grafting to Improve Dyeability and Wearability - Zhen Jiang; Xiao Wang; Yue Zhang; Haitao Ma; Lihua Lv; Yongzhu Cui; Guibing Pang (Journal of Natural Fibers, 2018)
Linen fabric was surface modified with acrylic acid (AA) and acrylamide (AM) using diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO) as photoinitiator via UV induced grafting to improve dyeing performance and wearability. Effects of different mass ratios of AA and AM in monomer mixture on dyeing performance and wearability were discussed. Maximum dye uptake of 79.4% of cationic dyes was achieved when AA was grafted only and 0/100 of AA and AM could be applied to dye a light color for good color fastness. Dyeing performance of grafted fabric was also improved with reactive dyes and direct dyes. In addition, breaking strength and rigidity of grafted fabric were improved.